De novo Transcriptome Analysis of Drought-Adapted Cluster Bean (Cultivar RGC-1025) Reveals the Wax Regulatory Genes Involved in Drought Resistance - Reddy, B. Manohara; Anthony Johnson, A. M.; Jagadeesh Kumar, N.; Venkatesh, Boya; Jayamma, N.; Pandurangaiah, Merum; Sudhakar, Chinta (Frontiers in Plant Science, 2022)
Cluster bean (Cyamopsis tetragonaloba L.) is one of the multipurpose underexplored crops grown as a green vegetable and for gum production in dryland areas. Cluster bean is known as relatively tolerant to drought and salinity stress. To elucidate the molecular mechanisms involved in the drought tolerance of cluster bean cultivar RGC-1025, RNA sequencing of the drought-stressed and control samples was performed. De novo assembly of the reads resulted in 66838 transcripts involving 203 pathways. Among these transcripts, differentially expressed gene (DEG) analysis resulted in some of the drought-responsive genes expressing alpha dioxygenase 2, Low temperature-induced 65kDa protein, Putative vacuolar amino acid transporter, Late embryogenesis abundant protein (LEA 3). The analysis also reported drought-responsive transcription factors, including NAC, WRKY, GRAS, and MYB families. The relative expression of genes by qRT-PCR revealed consistency with the DEG analysis. Key genes involved in the wax biosynthesis pathway were mapped using the DEG data analysis. These results were positively correlated with epicuticular wax content and the wax depositions on the leaf surfaces, as evidenced by SEM image analysis. Further, these findings support the fact that enhanced wax deposits on the leaf surface had played a crucial role in combating the drought stress in cluster beans under drought stress conditions. Also, this study provided a set of unknown genes and transcription factors that could be a source of engineering tolerance against drought stress in cluster beans.